GOSPF: An energy efficient implementation of the OSPF routing protocol. (November 2016) - D'Arienzo, M.; Romano, S.P.
Abstract: Energy saving is currently one of the most challenging issues for the Internet research community. Indeed, the exponential growth of applications and services induces a remarkable increase in power consumption and hence calls for novel solutions which are capable to preserve energy of the infrastructures, at the same time maintaining the required Quality of Service guarantees. In this paper we introduce a new mechanism for saving energy through intelligent switch off of network links. The mechanism has been implemented as an extension to the Open Shortest Path First routing protocol. We first show through simulations that our solution is capable to dramatically reduce energy consumption when compared to the standard OSPF implementation. We then illustrate a real-world implementation of the proposed protocol within the Quagga routing software suite.